End-of-Project report 'Broadening the scaling of Banana Xanthomonas Wilt (BXW) management in East and Central Africa' - Rietveld, Anne M. (2021)
Project start and end date: Jan 2018 – Dec 2020 NCE for Rwanda to 31-03-2020 Project leader: Boudy van Schagen / Anne Rietveld Project lead organization: Bioversity International Partners: National Agricultural Research Organisation (NARO), International Institute of Tropical Agriculture (IITA), Rwanda Agricultural Board (RAB), Institut National pour l'Etude et la Recherche Agronomiques (INERA), Inspection Provinciale de l'Agriculture, Pêche et Elévage (IPAPEL), DPEA Country(ies) of intervention: Uganda, Burundi, Rwanda, DR Congo Total budget: $563.474 Total co-investment: $133.527 and in kind